Surgical technology : principles and practice / Joanna Ruth Fuller ; Julie Armistead - Fuller, Joanna Ruth
Overview: Deliver the best patient care before, during, and after surgery with this straightforward, step-by-step guide to surgical skills and operating room procedures. It provides comprehensive coverage of all the updated AST Core Curriculum, 6th Edition components - health care sciences, technological sciences, patient care concepts, surgical technology, and surgical procedures. A mentoring approach makes even complex skills and techniques easy to understand. User-friendly features such as full-color illustrations, chapter outlines and summaries, review questions, critical thinking exercises, and technique boxes help you focus on the most important concepts and make it easier to retain and recall critical information. Chapter objectives correspond to the latest AST Core Curriculum objectives to ensure you have access to the most reliable information in the operating room